Challenges and Barriers Toward Medical Research Among Medical and Dental Students at King Khalid University, Abha, Kingdom of Saudi Arabia - Alsaleem, Safar Abadi; Alkhairi, Muhammed Alhussain Y.; Alzahrani, Mohammed Atiah A.; Alwadai, Mohammed Ibrahim; Alqahtani, Saad Saleh A.; Alaseri, Yahya Faye Y.; Alqarni, Mohammed Awadh M.; Assiri, Safiah Ahmad; Alsaleem, Mohammed Abadi; Mahmood, Syed Esam (Frontiers in Public Health, 2021)
Background: Medical research is a systematic method to obtain new knowledge, reduce diagnosis problems, discover the latest or best treatment for a disease, and also used for disease prevention. Objective: The study aims to assess the challenges and barriers to conduct medical research among medical and dentistry students and determine the reasons that hinder the conduct of the study. Methods: In this cross-sectional study, the research population consisted of medical and dental students affiliated with King Khalid University in Saudi Arabia in 2020. The study followed a descriptive approach based on quantitative analysis. The Statistical Package of the Social Sciences (SPSS) program (V. 16.0, SPSS Inc., Chicago, IL, USA) was used for data analysis. Results: A total of 327 students participated in this study, and the response rate was 100%. Among them, 61.5% were females. In this study majority (63.3%) had a moderate attitude towards conducting medical research and the average was 56.17. The majority (53.8%) had a reasonable behaviour towards conducting medical research, and the average was 29.06. Lack of time, skills, funding, facilities, and limited access to medical journals and related databases were the significant barriers found. Most of the students had positive attitudes, except that they are not awarded on their research, do not attend the sessions, and do not speak their thoughts. A significant relationship between demographic characteristics (age, level, and Grade Percentage Average), attitudes & perceived barriers toward research was found (<0.05). Conclusion: The majority of the students demonstrated a positive attitude towards and moderate behaviour of research. However, most are not awarded on their research, do not attend the sessions, and do not speak their thoughts. Intensive training and adequate support in research activities of medical and dental students at the undergraduate level may help reduce these challenges and barriers towards research.